A finite element model to predict the consequencesof endolymphatic hydrops in the basilar membrane - Areias, Bruno (2022)
Ménière's disease is an inner ear disorder, associated with episodes of vertigo,fluctuant hearing loss, tinnitus, and aural fullness. Ménière's disease is associ-ated with endolymphatic hydrops. Clinical evidences show that this disease isoften incapacitating, negatively affecting the patients' everyday life. The patho-genesis of Ménière's disease is still not fully understood and remains unclear.Previous numerical studies available in the literature related with endolym-phatic hydrops, are very scarce. The present work applies the finite elementmethod to investigate the consequences of endolymphatic hydrops in the nor-mal hearing, associated with the Ménière's disease. The obtained results forthe steady state dynamics analysis are in accordance with clinical evidences.The results show that the basilar membrane is not affected in the same inten-sity along its length and that the lower frequencies are more affected by theendolymphatic hydrops. From a clinical point of view, this work shows therelationship between the increasing of the endolymphatic pressure andthe development of hearing loss.